PENGARUH BEBAN PAJAK KINI, BEBAN PAJAK TANGGUHAN, TAX TO BOOK RATIO, DAN LEVERAGE TERHADAP KINERJA KEUANGAN (Studi Empiris Pada Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia 2021-2023) - SETYANINGSIH, INKA DWI; SYARLI, ZIKRI AIDILLA; RASMON, RASMON (JURNAL AKUNTANSI DAN KEUANGAN, 2024)
This research is a quantitative study that aims to determine the effect of current tax burden, deferred tax burden, tax to book ratio, and leverage on financial performance in pharmaceutical health sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. In determining the sample of this study using purposive sampling technique, so that 15 samples of companies that meet the criteria are obtained with three years of observation so that the total observations used in this study are 45 reports. This study uses secondary data obtained from the company's financial statements. The data analysis technique uses panel data regression analysis (pooled data) with the help of Eviews 12. The results showed that partially the current tax expense variable has a significant effect on financial performance, the deferred tax expense variable has no significant effect on financial performance, the tax to book ratio variable has a significant effect on financial performance, and the leverage variable has a significant effect on financial performance. From this study also obtained the coefficient of determination (R2) with a value of 0,6528, means that 65.28% of disclosure is explained by the variables between current tax expense, deferred tax expense, tax to book ratio, and leverage. While 34.72% is explained by other variables outside the model.